Factors Affecting Restaurants Selection In Coastal Area Of Tuminting Boulevard - Ivan Quilo; S. L. H. V. Joyce Lapian; Shinta J. C. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Many restaurant owners and family-owned businesses are increasingly looking forward to operating through this platform in order to increase sales. Hence, the online channels are frosting the foodservice sector in the country. They use the tools for market place in apps. But however, the group of family preferred to experience the restaurants have provide rather to use online services. This time the culinary place in coastal area is trending especially in Manado. The restaurant ready to open from day and night. Consumers freely to decide where they want to take lunch or dine-out according to the restaurant type. These restaurants are giving the sea view. The restaurant also supplies the menu in seafood, fast food, traditional food and etc. To full fill the consumer needs, restaurant provide some attributes like examples: WIFI, Air Conditioner (AC), parking lot, live music, VIP room, smoking area, photo spots, toilet and many more. Consumers are able to choose the seafood menu by their self. The culinary place in coastal area become favorite food place among the family, couples, teenagers and individuals if they want to eat with the landscape of the sea. The consumers can see location, missing clear information about the location, difficulties in reaching the distance etc. Restaurants that offer local products can respond to the expectations of the customers specially the view at Tuminting Boulevard.   Keywords: marketing, restaurant selection, factors analysis